The The Effect Of Gamification Method On Students' Understanding Of Concepts On Food Chain ​​Material In Social Natural Sciences in Elementary Schools - Muhammad Asrul Sultan; Muhammad Amran; Muhammad Rifky Darmawan (Jurnal Pendidikan Dasar dan Keguruan, 2026)
This study aims to investigate the effect of the gamification method on students' conceptual understanding of "Food Chain" topics within the IPAS subject (Natural and Social Sciences) at SD Muhammadiyah Parepare. A quantitative approach with a quasi-experimental, nonequivalent control group design was employed. The population included all Muhammadiyah elementary schools in Parepare, while the sample was selected via purposive sampling, consisting of 35 fifth-grade students: 18 in the experimental group (Class V.B) and 17 in the control group (Class V.A). Data were collected through a validated 30-item multiple-choice test and analyzed using the Independent Samples T-Test. The results revealed a significance value (2-tailed) of 0.000 (p < 0.05), leading to the rejection of the null hypothesis (H0​) and the acceptance of the alternative hypothesis (H1​). It is concluded that the implementation of the gamification method significantly enhances students' conceptual understanding of food chain material. These findings suggest that gamification serves as an effective pedagogical tool to improve students achievement in elementary science education.